A comparison of laboratory, clinical, and self-report measures of prospective memory in healthy adults and individuals with brain injury. Issue 5 (28th May 2018) - Raskin, Sarah A.; Shum, David H. K.; Ellis, Judi; Pereira, Antonia; Mills, Ginger
ABSTRACT: Individuals with traumatic brain injury (TBI) have demonstrated deficits in prospective memory (PM) functioning when compared to healthy adults. These deficits have been measured using laboratory measures, clinical measures, and self-report questionnaires. However, PM has been shown to involve multiple cognitive processes and have a variety of stages. Thus, it is not known whether these measures all assess the same aspects of PM. Thus, this study was designed to measure the convergent validity of the three types of PM measures in both healthy adults and individuals with TBI. We aimed to investigate the convergent validity of the three types of tasks in two ways. First, we sought to investigate whether the PM deficits experienced by people with TBI are consistent across tasks. Second, we sought to examine the relationship between the three types of tasks. Results demonstrated that while all three types of measures were sensitive to PM deficits in TBI, there were differences in the aspects/processes of PM being measured. Data from the laboratory measure suggested a specific difficulty with detecting the correct cue. Data from the clinical measure suggested that TBI has a greater effect on time-based cues than event-based cues and that the primary deficit is a prospective intention retrieval deficit rather than the retrospective memory component. In addition, those with TBI did not differ from healthy adults when the time delay was short enough, suggesting that PM is not universally impaired. Data from the self-report questionnaire suggested that those with TBI are more sensitive to difficulties with basic activities of daily living rather than instrumental activities on daily living. These results are discussed in terms of rehabilitation techniques that could focus first on cue detection and use basic activities of daily living as outcome measures.